Internalization of Qur'anic Influencers' Educational Values as a Pillar of Family Resilience against the Threat of Gaming Disorder - Nurfajri Siswi; Abdul Manan; Rahimah Embong (Islamic Studies and Civilization Journal, 2025)
The development of digital technology has changed family interaction patterns, notably reflected in the increasing cases of gaming disorder among children and adolescents, which can weaken the resilience of Muslim families by affecting behavior, spirituality, and parent-child relationships. This article aims to examine how the educational values ​​of Luqman al-Hakim in the Qur'an can be internalized as an educational approach to address this threat. This study employs a qualitative method with a thematic interpretation (tafsir maudhu'i), analyzing QS. Luqman 12–19 related to family education, self-control, and moral development. The findings indicate that values ​​such as strengthening monotheism, cultivating noble character, discipline in worship, emotional regulation, and persuasive communication play a strategic role in preventing addictive behavior toward digital games. Implementation includes family agreements on device usage, screen-free family time, integrating playful elements into worship activities, and continuous parental supervision. This approach not only limits technology use but also strengthens emotional and spiritual family bonds. Therefore, the internalization of Qur'anic education based on the example of Luqman al-Hakim is an effective strategy to build the resilience of Muslim families in the digital era.